Strategi Pengelolaan Akun Facebook Pemerintah Provinsi Nusa Tenggara Barat dalam Mendukung Keterbukaan Informasi Publik - Triwiyoso; I Ketut Putu Suardana (Indonesian Scientific Journal (Jurnal Ilmiah Indonesia), 2025)
This study discusses the strategy for managing the official facebook account of the Government of Nusa Tenggara Barat (Pemprov NTB) by the Public Information and Communication (IKP) division. The use of social media, particularly facebook, has become an essential tool for delivering public information in line with the mandate of Law No. 14 of 2008 on Public Information disclosure. This research adopts a qualitative approach using literature review, documentation, and direct observation methods. The findings reveal that strategic content planning, the use of data analytics, and engaging visual content are key to supporting information transparency. Additionally, rapid responses to public interactions and varied content, such as infographics and short videos, help increase public participation. This strategy not only strengthens information transparency but also builds public trust in the government. The study recommends optimizing social media management to create effective two-way communication between the government and the public.